pengaruh motivasi pelayanan publik terhadap kinerja pegawai dengan organizational citizenship behavior sebagai variabel intervening pada sinas tenaga kerja dan transmigrasi provinis jambi - Putri, Putri Maha Sari; Amin, Shofia; Sumarni, Sumarni (Journal of Business Studies and Management Review, 2024)
This research aims to examine and analyze the influence of public service motivation onemployee performance through organizational citizenship behavior. Using quantitative methods,data collection techniques are used through observation, questionnaires and documentation.Hypothesis testing was carried out using the Structural Equation Model (SEM) technique withthe smartPLS program. The research results show that: 1) public service motivation has apositive and significant effect on employee performance, 2) public service motivation has apositive and significant effect on organizational citizenship behavior, 3) organizationalcitizenship behavior has a positive and significant effect on employee performance, 4) Publicservice motivation has a positive and significant effect on employee performance withorganizational citizenship behavior as an intervening variable.Keywords: Employee Performance, Public Service Motivation, Organizational CitizenshipBehavior